ANALISIS STRUKTUR DAN DISTRIBUSI PENDAPATAN RUMAH TANGGA SERTA TINGKAT KESEJAHTERAAN ANGGOTA KOPERASI SERBA USAHA PETERNAK MOTIVASI DOA IKHTIAR TAWAKKAL (KSUP MDIT) DI KECAMATAN GISTING KABUPATEN TANGGAMUS - Fikri Syahputra; Dyah Aring Hepiana Lestari; Fembriarti Erry Prasmatiwi (Lampung University, 2018)
This study aims to analyze the household income’s structure and distribution, and the household welfare level among cooperatives members, in addition to analyze factors that affected the household welfare of cooperative members. This research employed case study method. The data was collected from September to October 2016. The research respondents were 55 people who were all members of KSUP MDIT. The data was consisted of primary and secondary data. Primary data was obtained by observation and interview; while secondary data was obtained from the agencies and literatures associated with the study. The data was analyzed by income analysis, income distribution analysis, welfare analysis and binnary logistic regression analysis. The result showed that the biggest member of cooperative member's household income structure in the latest year was non livestock earnings of On Farm followed by non farm income, goat business income and off farm income. Distribution of household member income of cooperatives were in low inequality. Based on Socio Metrix indicator, 70.91% cooperative members’ households were included in prosperous category and the remaining 29.09% were not prosperous and old variables of education, length of membership, and household income have a positive effect on welfare level.Key words: distribution income, prosperity of members, income